The Effect Of The 12% Vat Rate Increase Through Coretax System Against Income Of Umkm In Kediri City - Fadilla Rafida; Miladiah Kusumaningarti; Puji Rahayu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Study This aim For know influence tested variables​ to variables dependent through a series analysis statistics which include validity tests , reliability tests , assumption tests classic . Research methods use approach quantitative descriptive with data collection through questionnaire against 51 MSME sectors registered culinary​ as Taxable Entrepreneurs (PKP) at the Kediri Pratama Tax Office . All over instrument study stated worthy used Because every grains statement show mark correlation that exceeds the minimum limit so that can concluded to be valid. The test results reliability also shows that all over variables own level strong internal consistency so that the data is believed stable and able trusted . Testing assumptions classic show that the regression model has fulfil condition normality , no there is symptom multicollinearity , and residual variance in condition homoscedastic so that the model is assessed appropriate used in analysis continued . Regression results show that variables independent own significant influence​ to variables dependent Good in a way simultaneous and partial , which is proven through mark significance that is below the specified error limit . Research model This in a way overall assessed capable explain changes that occur in variables dependent , so that findings study can used as base consideration in taking decisions , development policies , as well as study next . Research This expected capable give contribution for understanding theoretical and practical related factors that influence variables studied​ as well as become reference for other relevant research .